LATAR BELAKANG PEMBENTUKAN KELOMPOK SOSIAL MAHASISWA PENDATANG (Studi Tentang Mahasiswa Pendatang Asrama Karimun Dang Melini Jalan Bangau Sakti, Pekanbaru) - Myatania Siska Putri Azri; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pekanbaru is one of the city accommodate many students from various areas. Along with thedevelopment of the times, human desire to be able to meet the needs of his education isincreasing, one a student of these symptoms generally realized with the left the origin andmoved into new areas, a student who did this often referred to migrants student. For a student ofthe migrants from the county Karimun this prefer to stay in hostels Karimun Dang Melini,Pekanbaru because in addition to the security themselves also feel familiar in his new and stillfeel being in a group of their own. In general that humans born to have and the group with otherhuman beings, it means that the survival of human took place with the atmosphere of supporteach other in together. Where each individual have dependency against the environment andother human beings. The addiction can be realized in social interaction that is the key of allsocial life, because without interaction won’t be there may be life together, so cause socialgroups in human life. According to the Josep S. Raucek and Roland L. Warren (1984), assertingthat the social groups is a group that includes two or more human, which among them there aresome of the interaction that can be understood by members or other people in its entirety. Thisstudy aims to know the factors that foregrounded the establishment of the social groups andactivities with conducted a student of the migrants in hostels Karimun Dang Melini, Pekanbaru,with the first figure out the relationship between individuals through the closeness sociometryand technique sociogram form of free. The theory used is the theory closeness, the theory reasonpractical, and the theory balance. Mothods used in writing this is qualitative descriptive, wherethe data that appears is the words that usually arranged in the form of the text that expanded.The techniques analysis of the data more using cross check information.Keywords: social groups, student migrant